Organochlorine Compounds in the Amur (Heilong) River Basin (2000-2020): A Review - Maksim M. Donets; Vasiliy Yu. Tsygankov (MDPI AG, 2023)
Persistent organic pollutants (POPs) are well-known contaminants that raise serious concerns, even more than 20 years after they were banned. Their worldwide distribution and persistence necessitate continuous monitoring in all components of the environment. The most challenging issues of POP regulation are associated with international water resources because their solutions require international cooperation in environment protection. This review provides data on various POPs (DDT, HCH, endrin, dieldrin, and PCBs) and their concentrations in aquatic organisms inhabiting the Amur River basin, one of the most poorly explored regions of Northeast Asia. Most studies have been conducted in the Songhua River (China), a tributary of the Amur River, which indicates that large inland bodies of water, especially those of international importance, require more extensive research.